Dendroglaciological investigations at Hilda Creek rock glacier, Banff National Park, Canadian Rocky Mountains - Carter, Rae; LeRoy, Sean; Nelson, Trisalyn; Laroque, Colin; Smith, Dan (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractDendroglaciological techniques are used to provide evidence of historical rock glacier activity at Hilda Creek rock glacier in the Canadian Rockies. The research focuses on the sedimentary apron of the outermost morainal deposit, where excavations in 1997 uncovered six buried tree boles that had been pushed over and entombed by distally spilled debris. Cross-sectional samples cross- dated with a local Engelmann spruce tree-ring chronology were shown to have been killed sometime after 1856. Based on the extent of the excavation, the data indicate that Hilda Creek rock glacier has continued to advance along the present ground surface at a rate exceeding 1 cm/year.